Predictors of blood pressure control in patients with resistant hypertension after intensive management in two expert centres: the Brussels-Torino experience. (3rd September 2019) - Pappaccogli, Marco; Di Monaco, Silvia; Georges, Coralie M.G.; Petit, Géraldine; Eula, Elisabetta; Ritscher, Sabrina; Lengelé, Jean-Philippe; Fanelli, Elvira; Severino, Francesca; Renkin, Jean; Avataneo, Valeria; Wallemacq, Pierre; et al.
Abstract: Background: Management of resistant hypertension (RHTN) is challenging and often implies the use of complex polypharmacy and interventional therapies. The main objectives of this study were (i) to describe the characteristics of patients with RHTN referred to two expert centres; (ii) to identify predictors of blood pressure (BP) control after intensive management. Methods: We reviewed electronic medical files of all patients referred for RHTN to the Brussels and Torino centres, and extracted detailed clinical data, informations on drug adherence and psychological profile. All patients with confirmed diagnosis of RHTN, according to office and ambulatory BP monitoring (ABPM) measurements, were considered eligible. Results: 313 patients (51% men; age: 56 ± 12 years; office BP 177/98 mmHg; 24-hour ABPM 153/90 mmHg) were included. At the end of follow-up (median: 2 years [1–4]), only 26% of patients ( n = 81) reached BP control. When compared to patients remaining resistant, patients eventually controlled had lower pulse pressure (71 vs. 82 mmHg, p < 0.001), less often myocardial infarction (6% vs. 20%, p < 0.005) and showed a higher recourse to cognitive reappraisal as far as emotion regulation is concerned (4.8 ± 1.1 vs. 3.9 ± 1.2, p = 0.009; ERQ Questionnaire). In a multivariate analysis looking for predictors of controlled BP, only the psychological characteristic of cognitive reappraisal (i.e., changing one's thoughts about a potentially emotion-eliciting event) remained significant (OR 2.06 [1.10; 3.84], p = 0.02). Conclusions: Even in expert centres, only a minority of patients with RHTN reached BP control, irrespective of the centre involved or the interventions applied. Patients who eventually responded to therapy had lower arterial stiffness and less cardiac organ damage. Furthermore, besides vascular damage, the single predictor of BP control was the ability to modify the emotional impact of stressful situations.